Southern African HIV Clinicians Society guideline on pre-exposure prophylaxis to prevent HIV - Pippa Macdonald; Gonasagrie Nair; Camilla Wattrus; Saiqa Mullick; Melanie Pleaner; Elzette Rousseau; Hasina Subedar; Dvora Joseph-Davey; Johan Hugo; Sinead Delany-Moretlwe; Linda-Gail Bekker (Southern African Journal of HIV Medicine)
No Abstract available.